Effects of a multi-professional intervention on body composition, physical fitness and biochemical markers in overweight COVID-19 survivors: a clinical trial - Sordi, Ana Flávia; Lemos, Maurício Medeiros; de Souza Marques, Déborah Cristina; Ryal, Joed Jacinto; Priscila de Paula Silva Lalucci, Marielle; Marques, Marilene Guiraldi; Amaro Camilo, Maria Luiza; De Paula Ramos, Solange; Franzói De Moraes, Solange Marta; Valdés-Badilla, Pablo; Mota, Jorge; Magnani Branco, Braulio Henrique (Frontiers in Physiology, 2023)
The sequelae post-COVID can affect different systems. In this sense, considering the multi-factorial etiology of COVID-19, multi-professional interventions could be a relevant strategy for recovery health indicators. Therefore, this study aimed to investigate the effects of multi-professional intervention on body composition, physical fitness, and biomarkers in overweight COVID-19 survivors with different symptomatology. A non-randomized parallel group intervention included 69 volunteers (BMI ≥ 25 kg/m2), divided into three groups according to SARS-CoV-2 symptomatology, but only 35 finished the longitudinal protocol [control group (n= 11); moderate group (n= 17) and severe group (n= 7)]. The groups were submitted to a multi-professional program (nutritional intervention, psychoeducation, and physical exercise intervention) for 8 weeks, and the volunteers underwent body composition assessments (primary outcome) and physical and biochemical tests (secondary outcome) in pre- and post-intervention. This study was registered on the Clinical Trials Registration Platform number: RBR-4mxg57b and with the local research ethics committee protocol under number: 4,546,726/2021. After the 8-week multi-professional intervention, the following results were observed for the moderate COVID-19 group: improved dynamic strength of lower- and (p=0.003), upper-limbs (p = 0.008), maximal isometric lumbar-traction strength (p=0.04), flexibility (p=0.0006), and albumin (p=0.0005), as well as a reduction in the C reactive protein (CRP) (p=0.003) and fasting glucose (p=0.001); for the severe COVID-19 group: an improvement in dynamic lower-body strength (p=0.001), higher values of albumin (p=0.005) and HDL-c (p=0.002), and lower values of C reactive protein (CRP) (p = 0.05), and for the control group: an improvement in sit-up repetitions (p=0.008), and a reduction of C reactive protein (CRP) (p = 0.01), fasting glucose (p = 0.001) and total cholesterol (p = 0.04) were identified. All experimental groups reduced triglycerides after intervention (p<0.05). Finally, 8 weeks of multi-professional intervention can be an efficient tool for reversing the inflammatory process and promoting improvements in daily activities and quality of life, although it is believed that the severe COVID-19 group needs longer interventions to improve different health indicators.